PENERAPAN ESKUL KEAGAMAAN UNTUK MENGEMBANGKAN BAKAT SISWA DI SDIT AD - DAUD PALARAN SAMARIND - Nurul Hikmah (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2022)
Education that only puts intellectual intelligence in reality is not enough as a provision in life. Having broad intellectual intelligence is a must-have obligation, because intellectual intelligence is a provision in the face of the development of the era. However, intellectual intelligence alone is not enough, because the ideals of Indonesian ancestors not only have broad intellectual intelligence. However, it is also a dignified nation, which has a noble character of ethics accompanied by religious values as a fortress in the students. The formation of religious characters can be done in various ways, one of them conducting religious activities at school, ranging from religious exclusions, Koran, training lectures and others. From this activity later the character of the students began to be well formed, who can not pay so can do the Koran, the rare prayers can be diligent prayers because in the school is required prayer in congregation depending on how we form the character of the student itself. Until later a good character will be brought by students to their neighborhood. The subject of this study is a class VI student of AD-DAUD Palaran, while the research object is the application of religious esules to develop talent. The data collection techniques used are observations, interviews and documentation. The study used the Miles and Huberman analysis model. Miles and Huberman, said that activities in the analysis of qualitative data are conducted interactively and continue continuously until complete, so that the data has been saturated. Keywords: Extracurricular, Religious, Talent